Effects of Enhanced External Counterpulsation With Different Sequential Levels on Lower Extremity Hemodynamics - Zhang, Yahui; Zhang, Yujia; Wang, Yinfen; Xu, Xiuli; Jin, Jing; Zhang, Xiaodong; Zhang, Wei; Wei, Wenbin; Zhong, Chubin; Wu, Guifu (Frontiers in Cardiovascular Medicine, 2021)
Objective: This study aimed to investigate hemodynamics of lower extremities during the Enhanced External Counterpulsation with three-level sequence at hips, thighs and calves (EECP-3), two-level sequence at hips and thighs (EECP-2) and single leg three-level sequence (EECP-1). Methods: Twenty healthy volunteers were recruited into this study to receive EECP intervention. Anterior tibial artery, posterior tibial artery and dorsalis pedis artery were imaged using Color Doppler ultrasound. Mean flow rate (FR), Area, pulsatility index (PI), Peak systolic velocity (PSV), end-diastolic velocity (EDV), mean flow velocity (MV) and systolic maximum acceleration (CCAs) were measured and calculated at baseline, during EECP-3, EECP-1 and EECP-2 in order. Results: PSV and EDV in the inferior knee artery significantly increased, and PI of posterior tibial and dorsalis pedis arteries also markedly increased among three protocols compared with baseline (all P<0.01). Additionally, EECP-3 significantly increased FR, MV and ACCs in the anterior tibial artery (all P<0.05). EECP-1 creates acute decrease in FR (P=0.014) and Area (P=0.003) of posterior tibial artery. Moreover, during EECP-2, PI of dorsalis pedis artery was significantly increased (P=0.002), while MV was markedly lower than that during EECP-3 (P=0.001) compared with baseline. Conclusion: EECP-3 creates acute improvement in the blood flow, blood flow velocity and ACCs of anterior tibial artery. By contrast, EECP-1 significantly reduces the FR and Area of posterior tibial artery, while EECP-2 mainly regulated the PI and MV of dorsalis pedis artery.